The Application of Prodrugs as a Tool to Enhance the Properties of Nucleoside Reverse Transcriptase Inhibitors - Fernandes, Lívia da Rocha [UNESP]; Lopes, Juliana Romano [UNESP]; Bonjorno, Andressa Francielli [UNESP]; Prates, João Lucas Bruno [UNESP]; Scarim, Cauê Benito [UNESP]; Dos Santos, Jean Leandro [UNESP] (MDPI, 2023)
Antiretroviral Therapy (ART) is an effective treatment for human immunodeficiency virus (HIV) which has transformed the highly lethal disease, acquired immunodeficiency syndrome (AIDS), into a chronic and manageable condition. However, better methods need to be developed for enhancing patient access and adherence to therapy and for improving treatment in the long term to reduce adverse effects. From the perspective of drug discovery, one promising strategy is the development of anti-HIV prodrugs. This approach aims to enhance the efficacy and safety of treatment, promoting the development of more appropriate and convenient systems for patients. In this review, we discussed the use of the prodrug approach for HIV antiviral agents and emphasized nucleoside reverse transcriptase inhibitors. We comprehensively described various strategies that are used to enhance factors such as water solubility, bioavailability, pharmacokinetic parameters, permeability across biological membranes, chemical stability, drug delivery to specific sites/organs, and tolerability. These strategies might help researchers conduct better studies in this field. We also reported successful examples from the primary therapeutic classes while discussing the advantages and limitations. In this review, we highlighted the key trends in the application of the prodrug approach for treating HIV/AIDS.
Keywords: AIDS; codrugs; HIV; medicinal chemistry; new drugs; nucleoside reverse transcriptase inhibitors (NRTIs); prodrugs